Protective effects of Lactococcus lactis subsp. lactis HFY14 supplementation on the brain, intestines, and motor function of antibiotic-treated mice - Yang, Yang; Zhao, Yuanji; Lei, Huan (Frontiers in Microbiology, 2024)
This study aimed to explore the anti-oxidative and anti-inflammatory properties of Lactococcus lactis subsp. lactis HFY14 (LLSLHFY14) and investigate its effects on the intestinal barrier, cranial nerve, and motor function in mice treated with antibiotics. Mice were administered an antibiotic mixture (neomycin 5 mg/mL, vancomycin 25 mg/mL, amphotericin B 0.1 mg/mL, ampicillin 10 mg/mL, metronidazole file 5 mg/mL, and lipopolysaccharide 1.5 μg/mL) intraperitoneally, and oxidative stress and inflammatory markers in the serum and brain tissues, and liver index were measured. H&E staining was performed to detect pathological alterations in brain tissues. The expression of intestinal-barrierrelated genes and that of genes involved in inflammatory pathways in the brain were detected using polymerase chain reaction (PCR). LLSLHFY14 administration extended the weight-loaded swimming and running times of mice and decreased the liver index. Moreover, the levels of malondialdehyde (MDA), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) in the serum and brain tissue were reduced, whereas those of superoxide dismutase (SOD), glutathione (GSH), and interleukin-10 (IL-10) were elevated. Elevated brain expression of the protein kinase B (AKT)/cAMP-response element binding protein (CREB)/brain-derived neurotrophic factor (BDNF)/extracellular signalregulated kinase 1 (ERK1) pathway, decreased brain expression of the IL-6 gene, and elevated cecum expression of zonula occludens-1 (ZO-1), occludin-1, and claudin-1 genes were noted. LLSLHFY14 supplementation significantly increased Bacteroidetes expression but decreased Firmicutes expression, thus increasing the Bacteroidetes/Firmicutes ratio. Overall, LLSLHFY14 supplementation ameliorated antibiotic-induced oxidative stress and inflammation in the mouse central nervous system, intestinal barrier dysfunction, and increased motor function, thus confirming its potential application as probiotics.